Aplicación de las artes plásticas como elemento potencializador de la creatividad y comunicación en los estudiantes de educación básica superior de la Unidad Educativa República del Ecuador en la ciudad de Machala. - Freire Calva, Yuri Yasmín (2015)
The subject investigated met the standards established by the Technical University of Machala, applying to go every step of the investigation, it has been developed for a general explanation of the problem under study, where development of the conceptual framework has been content have direct relation to the topic related to artistic expression as a means of enhancing creativity in the eighth grade students of the College of Basic Education High School Republic of Ecuador, Period 2013- 2014, based on this hypothesis were raised, which were tested by applying the tools of research such as survey of students, teachers and experts in visual arts, the results of the investigation focused on determining how creativity develops from artistic expression, the same as pointed, not apply artistic techniques to develop creativity and student to communicate what they think and feel.